Psychosocial Risk Factors, Burnout and Hardy Personality as Variables Associated With Mental Health in Police Officers - Talavera-Velasco, Beatriz; Luceño-Moreno, Lourdes; Martín-García, Jesús; García-Albuerne, Yolanda (Frontiers in Psychology, 2018)
Among the variables associated with occupational stress, the adverse perception of psychosocial risk factors in work and burnout have been some of the most studied. With the rise of Positive Psychology, other variables of individual type such as hardy personality have also been the subject of study. No studies have been found which jointly examine these variables to predict mental health in police officers. The aim of this research was to analyze which variables predicted mental health in police agents. A total of 223 policemen (202 men and 21 women) participated in a cross-sectional study. Of all the predicting variables, emotional exhaustion and perception of problems as challenges were the only factors introduced in the model that predicted perceived mental health. These factors must be considered to improve both human resource interventions and occupational health practices in this professional group